Determination of Chitin Content in Insects: An Alternate Method Based on Calcofluor Staining - Henriques, Bianca Santos; Garcia, Eloi Souza; Azambuja, Patricia; Genta, Fernando Ariel (Frontiers in Physiology, 2020)
Chitin is an aminopolysaccharide present in yeast cells and arthropod cuticle and is one of the most abundant biopolymers. The conventional methods for the quantitation of chitin content in biological samples are based on its hydrolysis (acid or enzymatic), and the assessment of the byproduct, glucosamine. However, previously described methodologies are time-consuming, laborious, low throughput, and not applicable to insect samples in many cases. Here we describe a new approach to chitin content quantitation based on calcofluor fluorescent brightener staining of samples, followed by microplate fluorescence readings. Calcofluor is a specific chitin stain commonly used for topological localization of the polymer. The protocol was tested in three important disease vector species, namely Lutzomyia longipalpis, Aedes aegypti, and Rhodnius prolixus, and then compared to a classic colorimetric chitin assessment method. Results show that chitin content in the tested insects can vary largely in a range of 8-4600 micrograms of chitin per insect, depending on species, sex, and instar. Comparisons between measurements from the previous protocol and calcofluor method showed statistically significant differences in some samples. However, the difference might be due to interference in the classic method from non-chitin sources of glucosamine and reducing agents. Furthermore, chitinase hydrolysis reduces the total chitin mass estimated between 36% and 74%, consolidating the fluorescent measurements as actual stained chitin in the same extent that was observed with the standard protocol. Therefore, the calcofluor staining method revealed to be a fast and reliable technique for chitin quantitation in homogenized insect samples.